Polyclonal Recipient nTregs Are Superior to Donor or Third-Party Tregs in the Induction of Transplantation Tolerance - Nina Pilat; Christoph Klaus; Karin Hock; Ulrike Baranyi; Lukas Unger; Benedikt Mahr; Andreas M. Farkas; Fritz Wrba; Thomas Wekerle (Journal of Immunology Research)
Induction of donor-specific tolerance is still considered as the “Holy Grail” in transplantation medicine. The mixed chimerism approach is virtually the only tolerance approach that was successfully translated into the clinical setting. We have previously reported successful induction of chimerism and tolerance using cell therapy with recipient T regulatory cells (Tregs) to avoid cytotoxic recipient treatment. Treg therapy is limited by the availability of cells as large-scale expansion is time-consuming and associated with the risk of contamination with effector cells. Using a costimulation-blockade based bone marrow (BM) transplantation (BMT) model with Treg therapy instead of cytoreductive recipient treatment we aimed to determine the most potent Treg population for clinical translation. Here we show that CD4+CD25+ in vitro activated nTregs are superior to TGFβ induced iTregs in promoting the induction of chimerism and tolerance. Therapy with nTregs (but not iTregs) led to multilineage chimerism and donor-specific tolerance in mice receiving as few as 0.5 × 106 cells. Moreover, we show that only recipient Tregs, but not donor or third-party Tregs, had a beneficial effect on BM engraftment at the tested doses. Thus, recipient-type nTregs significantly improve chimerism and tolerance and might be the most potent Treg population for translation into the clinical setting.